Evaluation of detachment methods for the enumeration ofBacteroides fragilis in sediments via propidium monoazide quantitative PCR, in comparison with Enterococcus faecalis and Escherichia coli - Kim, M. (2014)
Aims The aim was to develop an optimized detachment method for separating Bacteroidales from sediments to allow enumeration via PMA-qPCR. The effectiveness of four different detachment treatments in removing Bacteroides fragilis was compared as a function of time as well as in relation to Enterococcus faecalis and Escherichia coli as detected by cultivation and qPCR. Methods and Results Cells were inoculated into four sediments from sea water (SW) and freshwater (FW) beaches. Sediment samples were taken on days 1 and 7 and subjected to four different treatments for separation of micro-organisms. On day 1, the detachment treatments performed equally well in removing intact Bact. fragilis cells. In contrast, 7 days later the detachment treatment with Tween 80 and handshaking (TH) resulted in up to eightfold higher 16S rRNA gene concentrations of intact and total Bact. fragilis cells compared to other detachment treatments. Total Ent. faecalis cells based on the 23S rRNA gene were also preferentially recovered by treatment TH. Cultivable Ent. faecalis or E. coli numbers detached from sediments were similar for all methods in most sediments tested. Conclusions Handshaking and 1% Tween 80/NaOH (pH 7·0) eluant was the most efficient technique to recover intact as well as total Bact. fragilis cells in sediment samples with different salinities and after prolonged sediment cell contact time. Significance and Impact of the Study The optimized detachment method enables the application of PMA-qPCR to sediment samples to detect the presence of Bacteroidales cells and their DNA in future microbial source tracking studies.